Sequential and direct two-photon double ionization of D2 at FLASH (2009)
ABSTRACT: Sequential and direct two-photon double ionization (DI) of D2 molecule is studied experimentally and theoretically at a photon energy of 38.8 eV. Experimental and theoretical kinetic energy releases of D++D+ fragments, consisting of the contributions of sequential DI via the D2+(1ssg) state and direct DI via a virtual state, agree well with each other.